Thermochromic Glass Facades: A Sustainable Solution for Improving Buildings Energy Efficiency A Simulation-Based Study of an Office Building in Cairo, Egypt - Eslam Moraekip (JES: Journal of Engineering Sciences)
The built environment enhances human life, prompting architects and engineers to adopt innovative technologies for better building performance. Thermochromic glass has gained attention as a sustainable solution for improving energy efficiency by adjusting solar heat gains based on external temperatures. This study examines the energy performance of thermochromic glass in an office building in Cairo's new administrative capital, known for its hot-arid climate, using advanced simulation tools to compare its thermal and optical properties to conventional glazing systems including Design Builder Software Ltd. and Energy Plus, to analyze two distinct building scenarios: one with conventional glazing and the other using thermochromic glass technology. Both scenarios incorporated typical occupancy patterns, heating, ventilating, and air conditioning systems, to evaluate energy consumption, thermal comfort, and daylight performance. Study findings indicate that thermochromic glass significantly reduces cooling energy demand by limiting solar heat gain during peak temperatures while maintaining adequate daylight levels. It recorded remarkable reductions in solar heat gain through the building's external glazing system, achieving reductions of up to 90.18 % compared to buildings with conventional glazing. This translates to annual energy savings of up to 51.16 % compared to conventional glazing, highlighting its potential to decrease energy loads in areas with extreme heat. Additionally, this system enhances indoor thermal comfort by minimizing overheating and decreasing reliance on artificial cooling systems. The findings highlight the viability of thermochromic glass as a cost-effective and environmentally friendly technology for sustainable building design in hot-arid climates.